The Isoforms of Estrogen Receptor Alpha and Beta in Thyroid Cancer - Gong, Zhongqin; Yang, Shucai; Wei, Minghui; Vlantis, Alexander C.; Chan, Jason Y. K.; van Hasselt, C. Andrew; Li, Dongcai; Zeng, Xianhai; Xue, Lingbin; Tong, Michael C. F.; Chen, George G. (Frontiers in Oncology, 2022)
The incidence of thyroid cancer was predominant in women, indicating that the sex hormone may have a role in thyroid cancer development. Generally, the sex hormone exerts its function by binding to the correspondent nuclear receptors. Therefore, aberrant of these receptors may be involved in the development of thyroid cancer. Estrogen receptor alpha (ERα) and beta (ERβ), two main estrogen receptors, have been reported to have an important role in the pathogenesis of thyroid cancer. When the ERα and ERβ genes undergo the alternative RNA splicing, some ERα and ERβ isoforms with incomplete functional domains may be formed. To date, several isoforms of ERα and ERβ have been identified. However, their expression and roles in thyroid cancer are far from clear. In this review, we summarized the expressions and roles of ERα and ERβ isoforms in thyroid cancer, aiming to provide the perspective of modulating the alternative RNA splicing of ERα and ERβ against thyroid cancer.